Analysis of the Impact of Tofu Price Increases on the Purchasing Power of Tofu Sellers at Mardika Market, Ambon - Rahantoknam, Rugaya; Louhenapessy, William George; Sinay, Francisca Riconita (JENDELA PENGETAHUAN, 2023)
This study aims to determine the Increase in Tofu Prices Against the Purchasing Power of Tofu Traders in Ambon's Mardika Market. The type of research used in this research is descriptive quantitative research. Quantitative research is the data type that can be measured or calculated directly through information or explanations expressed in numbers or the form of numbers. The results of the research on the increase in tofu prices on the purchasing power of tofu traders at Mardika Ambon market used a simple regression test so that it can be seen that the increase in tofu prices on the purchasing power of tofu traders has a Standardized Coefficients value of 371, the correlation sign is (positive) meaning that the value of tofu price increases is good, so traders will also be satisfied and vice versa from the results of this study. It proves that the proposed hypothesis is accepted with a value of 0.22 ± 0.05; it can be concluded that there is an influence of variable X on variable Y or an increase in the price of tofu has a positive and significant effect on the significant purchasing power of tofu traders in the Mardika Ambon market.